The Role of Local Mass Media in Anticipating Hoax Information (Case Study at Radar Tasikmalaya) - Cakranegara, Doddy Iskandar; Ahmadi, Dadi; Kurnia, Septiawan Santana; Firmansyah, Firmansyah; Karsa, Satya Indra (Nyimak: Journal of Communication, 2023)
The proliferation of false information and hoaxes is significantly fueled by the rapid spread of unverified content on social media. This phenomenon poses a challenge to public trust and information integrity, underscoring the need for effective countermeasures. Journalism, particularly at the regional level, plays a crucial role in combating misinformation. This study investigates the role of local media, specifically Radar Tasikmalaya, a prominent news outlet in West Java, in addressing and countering hoaxes originating within its geographical area. Utilizing a qualitative case study approach, this research explores how regional journalism functions as a countermeasure to misinformation. Data collection involved in-depth interviews with Radar Tasikmalaya editors, observations of journalistic practices, and a documentation study of published news. Interviews provided insights into the editorial strategies and responsibilities assigned to journalists, while observations highlighted the reporting processes. The documentation study complemented these findings by analyzing how published content addresses and clarifies circulating hoaxes. The study finds that Radar Tasikmalaya plays a proactive role in maintaining information accuracy by assigning journalists the responsibility of fact-checking and clarifying misinformation. When erroneous information is identified, journalists are expected to promptly verify and correct it through their reports. This approach not only enhances public trust in the media but also underscores the journalists' social responsibility to provide accurate and reliable information to the community. The findings illustrate the critical role of local media in upholding journalistic standards and combating the spread of false information.Keywords: Journalism, local media, Radar, Tasikmalaya, anti-hoax ABTRAKPenyebaran informasi palsu dan hoaks secara signifikan dipicu oleh penyebaran konten yang belum diverifikasi di media sosial. Fenomena ini menjadi tantangan bagi kepercayaan publik dan integritas informasi, yang menekankan perlunya langkah-langkah penanggulangan yang efektif. Jurnalisme, terutama di tingkat regional, memainkan peran penting dalam melawan misinformasi. Penelitian ini menyelidiki peran media lokal, khususnya Radar Tasikmalaya, sebuah media berita terkemuka di Jawa Barat, dalam menangani dan melawan hoaks yang berasal dari wilayah geografisnya. Dengan pendekatan studi kasus kualitatif, penelitian ini mengeksplorasi bagaimana jurnalisme regional berfungsi sebagai langkah penanggulangan terhadap misinformasi. Pengumpulan data dilakukan melalui wawancara mendalam dengan editor Radar Tasikmalaya, observasi praktik jurnalistik, dan studi dokumentasi berita yang telah diterbitkan. Wawancara memberikan wawasan mengenai strategi editorial dan tanggung jawab yang diberikan kepada jurnalis, sementara observasi menyoroti proses pelaporan berita. Studi dokumentasi melengkapi temuan ini dengan menganalisis bagaimana konten yang diterbitkan menangani dan mengklarifikasi hoaks yang beredar. Penelitian ini menemukan bahwa Radar Tasikmalaya berperan proaktif dalam menjaga akurasi informasi dengan menugaskan jurnalis untuk melakukan pengecekan fakta dan mengklarifikasi misinformasi. Ketika informasi yang salah teridentifikasi, jurnalis diharapkan untuk segera memverifikasi dan mengoreksi melalui laporan mereka. Pendekatan ini tidak hanya meningkatkan kepercayaan publik terhadap media, tetapi juga menekankan tanggung jawab sosial jurnalis dalam menyediakan informasi yang akurat dan dapat dipercaya bagi masyarakat. Temuan ini menggambarkan peran penting media lokal dalam menjaga standar jurnalistik dan melawan penyebaran informasi palsu.Kata Kunci: Jurnalistik, media lokal, Radar, Tasikmalaya, anti hoax